2020
DOI: 10.1007/s40430-020-02690-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-responses optimization of finishing honing process for surface quality and production rate

Abstract: The finishing honing process is an effective machining to enhance surface properties. The objective of this work is to optimize the machining parameters, including the tangential speed (H), linear speed (L), and grit size (G) for minimizing the average roughness (R a ), maximum height roughness (R y ), and machining time (T M ). The honing experiments were performed with the aids of an industrial machine and the Box-Behnken experimental matrix. The nonlinear relationships between machining parameters and honin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Taking the dimensions of carbide anvil system as input variables, the mass, maximum temperature, maximum contact and shear stress are defined as target variables. The sensitivity analysis of carbide anvil size parameters is carried out in order to find out the parameters that have a greater impact on the target variables [30][31][32][33]. In order to ensure that there will be no interference when the size of parts changes, the same fitting size of each part is expressed by the same variable parameter.…”
Section: Sensitivity Analysis Of Carbide Anvil Sizementioning
confidence: 99%
“…Taking the dimensions of carbide anvil system as input variables, the mass, maximum temperature, maximum contact and shear stress are defined as target variables. The sensitivity analysis of carbide anvil size parameters is carried out in order to find out the parameters that have a greater impact on the target variables [30][31][32][33]. In order to ensure that there will be no interference when the size of parts changes, the same fitting size of each part is expressed by the same variable parameter.…”
Section: Sensitivity Analysis Of Carbide Anvil Sizementioning
confidence: 99%
“…Step 4: The DA is applied to identify optimal values of process parameters and responses, in which each burnishing response is transformed into the function of the desirability (di) [23]. The desirability values are computed for three cases, including the maximum, minimum, and constrained objectives.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…In recent years, the empirical study of market price predictability has promoted the rise of behavioral finance. For example, Sargun et al [16] found that the price fluctuation in the U.S. stock market is too large to be explained by fundamental information; When Nguyen and Duong [17] studied the stocks on the New York Stock Exchange, they found that the stocks with the best performance in three to five years will have the lowest market adjusted return in the same period of time; Coba Salcedo et al [18] found that the dividend price ratio can significantly predict the future yield; and Pembury Smith and Ruxton [19] found that trading strategies based on price momentum over the past 3 to 12 months can obtain excess returns. In addition, many other studies have found that financial markets are predictable.…”
Section: Related Workmentioning
confidence: 99%